2006
DOI: 10.21273/hortsci.41.7.1541
|View full text |Cite
|
Sign up to set email alerts
|

Crop Load Affects Vegetative Growth Flushes and Shoot Age Influences Irreversible Commitment to Flowering of `Hass' Avocado

Abstract: Several studies were undertaken in commercial nonirrigated `Hass' avocado orchards under the subhumid semiwarm subtropical climate of the state of Nayarit, Mexico, with the following objectives: 1) to determine the frequency and intensity of vegetative shoot flushes and their contribution to the production of floral shoots, 2) to quantify the effect of tree fruit load on the occurrence of vegetative shoot flushes during the year and the relationship between vegetative and reproductive shoot number duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
5
0
6
Order By: Relevance
“…Peach trees cultivated in these regions may present difficulties for promoting and suspension growth, what will account for problems regarding the normal flow of the so-called circadian cycle of plants throughout the year. Under vegetative growing conditions in tropical regions, tree growth may occur in the form of "vegetative growth flushes", which may vary in number of occurrence, intensity and duration, according to the time of year, or to environmental/hormonal stimulus received by plants like what occurs in other plant species such as mangoes and avocado trees (Yeshitela et al, 2004;Salazar-García et al, 2006). The occurrence of these "flushes" may alter the establishment of the total leaf area and also of the individual leaf area of the leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Peach trees cultivated in these regions may present difficulties for promoting and suspension growth, what will account for problems regarding the normal flow of the so-called circadian cycle of plants throughout the year. Under vegetative growing conditions in tropical regions, tree growth may occur in the form of "vegetative growth flushes", which may vary in number of occurrence, intensity and duration, according to the time of year, or to environmental/hormonal stimulus received by plants like what occurs in other plant species such as mangoes and avocado trees (Yeshitela et al, 2004;Salazar-García et al, 2006). The occurrence of these "flushes" may alter the establishment of the total leaf area and also of the individual leaf area of the leaves.…”
Section: Resultsmentioning
confidence: 99%
“…The months where the buds grew best were from June to September for the three materials; this coincides with the rainy season and with increasing temperature. y dependiendo de las condiciones climáticas, así como de la carga de fruto en el árbol, se pueden presentar de dos a cuatro flujos al año (Salazar-García et al, 2006).…”
Section: Resultsunclassified
“…In mango, Avilan et al (2000) observed that, the bud growth is rhythmic with three or four vegetative flows from 30 to 40 days of duration each year, but this feature can be modified by pruning, since pruned-trees develop up to four growth streams in nine months, while non-pruned trees had one or two streams. In avocado, growth also occurs as vegetative flows depending on weather conditions and the load of fruit on the tree, there may be two or four flows per year (Salazar- García et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The biomass production differs compared to non-harvested trees, especially for black locust [33]. To account for this, specific yield tables and growth models for coppices of different broad-leafing tree species were developed [34][35][36][37][38][39][40][41][42][43][44][45][46]. Moreover, in nutrient-poor and sandy forest stands, a decreasing number of black locust stump shoots with increasing shoot age and a wide variety of stump shoots depending on the stump distance and stump age was observed [47,48].…”
mentioning
confidence: 99%